Bulb Mites Rhizoglyphus echinopus (Fumouze and Robin) Associated with Subterranean Termite (Isoptera) in Brazil - Silva, Ademar Ferreira; Pinto, Zeneida Teixeira; Caetano, Rebecca Leal; Carriço, César; Sato, Tayra Pereira; Amorim, Marinete; Gazeta, Gilberto Salles (EntomoBrasilis, 2016)
Abstract. Four bulb mites deutonymphs (hypopus) from Rhizoglyphus echinopus (Fumouze & Robin) (Acari: Acaridae) were found attached to the head of a subterranean termite belonging to Coptotermes genus in Rio de Janeiro, Brazil. These mite species are commonly associated with ornamental plants and trees with bulbs, corms and tubers. All four hypopus were found attached to the surface of termite’s head. Results from this study provided an insight on the phoretic relationship of mites and termites, indicating the role of the latter in the dispersion of the first. Ácaros do Bulbo Rhizoglyphus echinopus (Fumouze and Robin) Associados com Cupim Subterrâneo (Isoptera) no Brasil Resumo. Quatro deutoninfas de ácaros do bulbo (hipopus) da espécie Rhizoglyphus echinopus (Fumouze & Robin) (Acari: Acaridae) foram encontradas fixadas na cabeça do cupim subterraneo pertencente ao gênero Coptotermes no Rio de Janeiro, Brasil. Estas espécies de ácaros estão comumente associadas a plantas ornamentais e plantas com bulbos e turbéculos. As quatros hipopus foram encontradas fixadas na superfície da cabeça do cupim. Os resultados desse estudo fornecem uma visão sobre a relação forética de ácaros e cupins, indicando o papel deste último na dispersão do primeiro.